ANTIDIARRHEAL MECHANISM AND IONIC PROFILE OF CARPOLOBIA LUTEA ETHANOLIC STEM-BARK EXTRACT IN RATS - Nwidu, Lucky Legbosi; Ukiri, Orodje Onomor; Rodrigues, Clenilson Martins [UNESP]; Vilegas, Wagner [UNESP] (African Networks Ethnomedicines, 2014)
Background: The stem-bark extract of Carpolobia lutea ( Polygalaceae), used in ethno-medicine as anti-diarrhea was pharmacologically evaluated. This was the first report of assessment of the ethanolic stem extract (ESE), of C. lutea as anti-diarrhoeal agent in rats. The anti-diarrhoeal effects, acute toxicity and ionic profile are investigated and reported.Materials and Methods: The acute toxicity was established using Lock's method. The anti-diarrhoeal effects were demonstrated using castor oil-induced diarrheal and fluid accumulation and its effect on normal intestinal transit. The mechanism elucidated using yohimbine, isosorbide dinitrate, and diphenoxylate. The elemental and ionic profile of ESE was established using inductively coupled argon-plasma emission spectrometer and potentiometric titration respectively. The finger print of ESE was revealed by Jasco (Tokyo, Japan), HPLC and active compounds by phytochemical screening using standard procedure.Results: The LD50 obtained is 866.025 mg/kg (i.p). The doses of 43.3, 86.6, and 173.2 mg/kg of ESE showed inhibition of castor oil-induced diarrheal (p<0.05 - 0.001). The most abundant cations in the extract are potassium and phosphorus (1.00 +/- 0.01 and 0.80 +/- 0.030 mg/g respectively); while the most abundant anions are phosphate and sulphate (33.50 +/- 7.09 and 7.19 +/- 3.29 mg/g respectively). The HPLC fingerprint of ESE revealed UV spectra of biomolecules. Phytochemical screening revealed presence of saponins, polyphenols and glycosides.Conclusion: These investigations indicate presence of bioactive and elemental substances which could play major role in diarrheal management. This investigation justifies the use of stem-bark of C. lutea in illicit gin (akpatashi), among the Effiks in Nigeria as antidiarrheal.
Keywords: Carpolobia lutea; stem-bark extract; antidiarrheal; elemental and ionic profile